Liquidity Management and Financial Performance of Nepalese Commercial Banks - Sah, Shreeram; Lertjanyakit, Hatairat (Nepalese Journal of Management Science and Research, 2019)
This study investigates the impact of liquidity management on the financial performance of Nepalese commercial banks. The study finds that LR has significant positive relationship with market value of financial performance, whereas CRR has significant negative relationship with market value of financial performance. The results also revealed that CDR and LR has significant negative relationship with book value of financial performance, whereas capital adequacy ratio has positive significant relationship with book value of financial performance.